Instant messaging application usage for clinical consultation among orthopedic surgery residents in Turkey: A survey study - KÜÇÜKDURMAZ, FATİH (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: This study aimed to determine the characteristics of instant messaging application (IMA) usage for clinical consultation among orthopedic residents in Turkey and to explore their experiences and opinions concerning potential legal problems. Methods: A questionnaire titled Instant messaging for consultation among orthopedic surgeons consisting of 21 questions was applied to orthopedic surgery residents, and the results were analyzed. The questions were designed to obtain information on 4 categories: 1) demographics and professional experience. 2) attitudes on the use of cellular phones. 3) MA usage for clinical consultation purposes, and 4) problems and comments on smartphone application usage for clinical consultation purposes. The participants who had no experience with a smartphone or IMA usage were excluded at the final analysis. Results: A total of 860 orthopedic residents (849 males [98.7%]; mean age = 28.6 years; age range=22-44 years) participated in the survey (participation rate: 97.3%). The distribution of residency years was as follows: 1st year, 27%; 2nd year, 21.4%; 3rd year, 18.4%; 4th year. 17.4%; and 5th year. 49.9%. The most frequently used IMAs were WhatsApp (99.3%), Facebook Messenger (14.8%), Viber (8%). and Tango (1.3%). The rate of IMA usage for consultation was 95.3%. The most common reasons to prefer IMAs for consultation were being fast and easy, but only 26.3% of the residents reported that they prefer the use of IMAs because they find them reliable. Moreover, 41.7% of the respondents reported that they had an experience of misdiagnosis owing to the use of IMAs; 81.2% of the participants used the personal information of the patients during the consultation; 57.6% of the respondents considered that legal problems may arise because of the use of IMAs during the consultation; and 51.4% believed that an electronic platform, solely for consultation purposes, is required. Conclusion: This survey has shown that it is necessary to make some legal regulations regarding the use of IMAs for consultation purposes and to develop applications only for medical consultation purposes. Most of the trainees make decisions using IMAs without a proper examination, putting the patients at the risk of misdiagnosis. Moreover, the confidentiality of the patient's personal information appears to be in danger when IMAs are used.
Keywords: Instant messaging applications; Teleconsultation; Privacy; Confidentiality; WhatsApp; WHATSAPP; RELIABILITY; COMMUNICATION